Evaluation of Subclinical Systolic Dysfunction in Patients with Heart Failure with Preserved Ejection Fraction, Using 2D Speckle Tracking Echocardiography - Siraj, Mohamed Mausool; Anwar, Afm Azim; Hashan, Md Nazmul; Rana, Masud; Parvin, Tanjima; Mohammed, Noor; Ansari, Sanjida; Rahman, Mohammad Walidur; Mandal, Mohammad Rayhan Masum; Ahmed, Chaudhury Meshkat (University Heart Journal, 2025)
Background: Originally thought to be purely due to LV diastolic dysfunction, studies according to western countries have suggested that heart failure with preserved ejection fraction (HFpEF) is more complex. In patients with HFpEF, global LV systolic function is commonly considered normal as the global ejection fraction (EF) is normal. However, the EF reflects only the global cardiac contractile function and does not take the subclinical systolic function into consideration. Therefore, more attention should be paid on this subset of heart failure population in which the frequency of subclinical systolic dysfunction has not been clearly identified. Objective: The principal objective of this study was to assess the global longitudinal systolic function of the LV in Bangladeshi patients with HFpEF using from 2D speckle tracking echocardiography. Methods: This study was conducted from May 2018 to April 2019 in department of cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. A total of 31 patients with HFpEF were enrolled in the study. Detailed history was taken including NYHA functional class, relevant physical examinations and investigations were done. 2D echocardiography, color Doppler, tissue Doppler and 2D speckle tracking echocardiography were done. GLS was obtained in a total of 31 patients with HFpEF diagnosed according to the 2016 European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of acute and chronic heart failure. Result: All patients with HFpEF had preserved LV ejection fraction (LVEF>50%) and evidence of diastolic dysfunction. Majority of study subjects had reduced GLS when -18% was used as the lower limit of normal as per vendor specific recommendations. Conclusion: Subclinical systolic dysfunction was frequent in the majority of HFpEF patients. Further large-scale studies are recommended to confirm the findings of this study. University Heart Journal 2024; 20(1): 3-9